ISOLATION OF Papulaspora halima AND A NEW MORPHOLOGICAL VARIETY OF Halosphaeria tubulifera FROM SEAWATER OF POTTER COVE (KING GEORGE ISLAND, SOUTH SHETLAND ISLAND, ANTARCTICA - Stchigel, Alberto; Calduch, Misericorda; Guarro, Josep; Ruberto, Lucas; Mac Cormack, Walter (Boletín Micológico, 2009)
Marine fungi arscribed to the ascomycetes and the hyphomycetes are infrequently reported for the Southern Ocean. For this reason, the main objectiv of the present work was to detect the presence of these fungi seawater of Potter Cove, King George (25 de Mayo) Island, South Shetland Island, Antarctica.